Workshop on State of Foresight in the CGIAR - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2018)
This report captures outcomes of the State of Foresight in the CGIAR workshop (https://cas.cgiar.org/isdc/events/international-workshop-state-foresight-cgiar), held in Aberdeen, 9-10 May 2018. The aims of the workshop were to take stock and synthesize the recent foresight activities and findings in the CGIAR, and discuss the conclusions of the independent foresight assessment led by ISPC in 2017 and their implications for the R4D strategies of the CGIAR.